EFFECTIVENESS OF THE MEDICAL WASTE MANAGEMENT INTERVENTION PROGRAM AT THONG NHAT HOSPITAL IN 2024 - Thị Tiến, Nguyễn; Xuân Quảng, Đoàn; Thị Ngần, Đoàn; Thị Hà Trang, Lê; Thị Thắm, Nguyễn; Thị Hoa, Vương; Thành Toàn, Võ (Journal of Health and Aging, 2025)
To evaluate the effectiveness of the medical waste managementintervention program at the Department of Traumatology - Orthopedics and the Department of Urology, Thong Nhat Hospital in 2024. Intervention study, conducted on 31 nurses in two departments. The intervention program includes: knowledge training, distribution of medical waste classification instruction cards, improvement of classification means, and increased monitoring. The effectiveness is assessed through changes in knowledge, attitudes, practices, and costs of medical waste treatment before and after the intervention. After the intervention, the proportion of nurses with high knowledge increased from 0% to 96.8%, and satisfactory practice from 41.9% to 83.9% (p < 0.01). Waste treatment costs decreased by 30.8% thanks to correct classification. However, attitudes did not change significantly (p = 0.54). The factor of seniority is related to knowledge and practice (p < 0.01). The intervention program has significantly improved nurses’ knowledge and practice in classifying medical waste, contributing to a reduction in the cost of waste treatment in hospitals. This program needs to be expanded and maintained regularly.
Keywords: medical waste; waste management; nursing